Perancangan Roda Gigi Miring Pada Transfer Case Jimmy - M. Alfi Nugraha; Kardiman; Oleh (Jurnal Serambi Engineering, 2024)
The design of the bevel gear in the Suzuki Jimny transfer case is a crucial part of developing the transmission system for this vehicle. The bevel gear is responsible for transferring motion and torque between the pinion and the drive gear, ensuring efficient power delivery and high reliability under various operating conditions. The design process includes the selection of the gear module, the number of teeth and critical angles such as the pressure angle and bevel angle, all of which affect the performance and strength of the gear. The selection of the right materials is also an important consideration to achieve optimum levels of strength and durability. By integrating technology and advanced design methodology, the design of the bevel gear in the Suzuki Jimny transfer case not only guarantees high performance, but also takes into account aspects of efficiency and durability in the use of materials and energy. The results of this design are expected to improve the overall performance of the Suzuki Jimny transfer case, make an important contribution to the development of automotive technology, and form the basis for further research in this field of the design and manufacture of precision engine components.